A study to assess the effectiveness of clinical teaching on the level of knowledge regarding nursing care bundle to prevent ventilator associated pneumonia among ICU nursing officers at AIIMS Bhopal - Verma, Ranjana; Phalswal, Uma; Joseph, Sneha; Nanhelal, Yadav Pooja; Kumari, Shalu; ., Sharda; Kumari, Sapna; Kumari, Seema; Rani, Guriya (International Journal of Research in Medical Sciences, 2024)
Background: Healthcare is a professional area bound to the ethical foundation of “do no harm.”, But in the current scenario, a rush to promote the curative scenario has led to the total downplay of the preventive aspect of care. The aim of this study was to assess the knowledge regarding nursing care bundle for the prevention of VAP among nursing officers before and after clinical teaching and to evaluate the effectiveness of clinical teaching. Methods: This pretest-post-test study was conducted on nursing officers working in the ICU of the All-India Institute of Medical Sciences, Bhopal, Madhya Pradesh. 100 nursing officers were enrolled in the study via convenience sampling technique. The self-structured tool was validated by 10 experts with a mean CVI value of 0.94. The reliability of the self-structured knowledge questionnaire was determined by the test-retest method and found to be 0.87. The collected data was analysed for frequency, mean, standard deviation, t-test, and association. Results: Findings showed that the mean knowledge score was 18.46±3.543 before intervention. After the intervention of video-assisted clinical teaching, a post-test was conducted, and the mean post-test knowledge scores was 25.07±2.801 at the p value <0.01. Knowledge of subjects about nursing care bundle for prevention of VAP was found to have a significant association with only educational qualification. Conclusions: This study’s findings concluded that educational interventions are necessary for the enhancement of knowledge and better compliance of nursing officers with guidelines regarding the bundle of care for the prevention of ventilator-associated pneumonia.